Scooby-Doo! World of Mystery 13 Portugal-Tower of Belem - Craft Plus Publishing Ltd (De Agostini Uk Ltd, 2004)
A sea monster is causing chaos at the harbour - but something fishy is going on!The gang investigate...
Keywords: Juvenile literature-Fiction